The illusion of progress in nursing - Herdman, Elizabeth A. (Nursing philosophy, 2001)
The notion that history is a record of continuous improvement has come to dominate the Western view of the world. This paper examines how nursing has embraced this ‘Enlightenment project’ and continues to be guided by a faith in ‘history as progress’ despite the fact that its structural position remains one of subordination and struggle. Faith in progress is manifested in nursing historiography and contemporary nursing literature, in the basic tenet of nursing orthodoxy, that professionalization is both inevitable and desirable, in the alignment of nursing with medical science and technology and the belief that Western nursing is the model for nursing world wide. It is argued that this uncritical faith in a continuously improving future has obscured nursing's vision for the future and rendered it powerless in the face of rapid global economic and social change.